The impact of location on firm growth - David B. Audretsch; Dirk Dohse (Centre for Economic Policy Research (CEPR), 2004)
This Paper links the performance of new technology firms, measured in terms of growth, to geographic location. We introduce a model of firm growth that is specific to characteristics of the location as well as the firm and industry. The model is estimated using a new dataset identifying the growth performance of small technology-based firms. In fact, firm performance, as measured by employment growth, does appear to be influenced by locational characteristics as well as characteristics specific to the firm and the industry. In particular, the empirical evidence suggests that being located in an agglomeration rich in knowledge resources is more conducive to firm growth that being located in a region that is less endowed with knowledge resources. These results suggest the economic value of location as a conduit for accessing external knowledge resources, which in turn, manifests itself in higher rates of growth.
Keywords: L10; O12; O30; R11; 330; Betriebliche Standortwahl; Betrieblicher Standort; Unternehmensentwicklung; Wissenstransfer; Spillover-Effekt; Deutschland